О нашем многолетнем творческом содружестве - Сердюк, А. С.; Зинченко, Елена Константиновна; Смецкова, Н. А.; Панченко, Т. Р. (Факт, 2017)
В статье представлены данные о многолетнем сотрудничестве коллектива санатория и кафедры в подготовке врачей для санатория, улучшении лечебного процесса и об общих научных исследованиях.

The article presents data on the long-term cooperation of the staff of the sanatorium and the department in the preparation of doctors for the sanatorium, improvement of the medical process and joint research.
About our long-term creative friendship
Keywords: санаторий; кафедра; сотрудничество; успехи; лечение; обучение; sanatorium; department; cooperation; successes; treatment; training